Vanuatu : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Vanuatu has a comparatively favorable economy and cautious macroeconomic policies that have helped maintain stability and confidence. Financial sector policies also have been appropriately cautious. The economy must maintain low debt in the longer term, but as funding is needed for infrastructure, maintenance, and social services, new revenue measures have to be identified. This revenue could help strengthen the state while maintaining growth potential, especially in the tourism and agricultural sectors. The financing options for new large infrastructure projects have to be assessed.